Analysis Ideational Metafunction In Recount Text At SMAN 1 Panai Hilir Labuhanbatu, Sumatera Utara - Madya Ramadhani; Joyce Kezia Nainggolan; Delfia Magdalena Sitompul (Jurnal Ilmu Pendidikan dan Sosial, 2023)
This study aims to test the most common ideational metaph function in the composition of the student recount text downstream of SMA Negeri 1. The purpose of this study is to characterize the conditions and dominant processes that arise in the text of the story again. The research design used by the author is a qualitative descriptive technique. Through the preparation of recount text by students, data are analyzed and collected. Ten manuscripts are examined and categorized. Researchers examine recount writing using transitivity analysis as a tool. Data analysis reveals that the material process is the most common type of process in writing recount. It appears 66 times (or 40%) in student writing about account papers. It refers to procedures, actions, physical matters, or both. The results of this study are dominantly present in the recount text is one of the time, which provides information about actions and periods by answering the question "where, when, and how".